A rare case report on uterine perforation by levonorgestrel releasing intrauterine device - Vijaykumar C. R.; Asha C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
A levonorgestrel-containing intrauterine contraceptive devices are widely used in contemporary gynaecology, primarily as an effective method for contraception and for control of menstrual disorders like menorrhagia and dysmenorrhea. A case report of the uterine perforation by the levonorgestrel-releasing intrauterine device (LNG-IUD) in a 33-year-old asymptomatic woman after an 18-month of insertion. On routine cervical smear examination, the LNG-IUD threads were not visualised through the cervical os. After abdominal ultrasound scan the confirmation of perforated LNG-IUD was done and was removed laparoscopically.